The jurisprudential corpus and the history of Ibadism in medieval Libya: additions and difficulties / استغلال المدوّنة الفقهيّة الإباضيّة في دراسة تاريخ ليبيا الوسيط بين الإضافات والصعوبات: كتاب اللقط نموذجا - Khlifi, Houcine (LibMed, 2024)
Houcine KHLIFI (University of Sousse, Tunisia) Introduction This study questions the relations between fiqh and history through the lense of Kitāb al-Luqaṭ by al-Šammāḫī. According to al-Warǧilānī, the imam Abū l-Ḫaṭṭāb established the first Ibāḍī emirate near Tripoli (in Ṣayyād) in 140/757. Later, in the...
Keywords: Fiqh -- Libye -- 8e siècle

The jurisprudential corpus and the history of Ibadism in medieval Libya: additions and difficulties - Khlifi, Houcine (Réécrire l’histoire de l’espace libyen au Moyen Âge, 2024)
Keywords: Fiqh -- Libye -- 8e siècle